Preliminary Geological Map and Description of the Himalaya-Karakorum Junction in Chogo Lungma to Turmik Area (Baltistan, Northern Pakistan) - Fort, Patrick Le; Lemennicier, Yves; Lombardo, Bruno; Pecher, Arnaud; Pertusati, Piero; Pognante, Ugo; Rolfo, Franco (Journal of Nepal Geological Society, 1995)
Some 800 km2 of the area lying between the Hararnosh Spur of the Himalaya and the Southern Karakorum Complex, centered on the Chogo Lungma glacier system, is presented on a preliminary geological map, after three expeditions. It includes three major units from SW to NE: the High Himalayan Nanga Parbat - Haramosh Crystallines (HHC), the Ladakh Paleo Island Arc, and the Karakorum Metamorphic Complex intruded by granitoids. The three units are thrust to the south. The High-Himalayan ortho- and para-gneisses are metamorphosed to granulite facies and migmatised. The Ladakh Arc is made up of two groups of formation, the Askore Amphibolite to the SW and the Greenstone Complex to the NE, separated by a screen of serpentinized ultramafics. It is intruded by numerous granitoids including a leuco-trondhjemite body cutting the Himalaya-Ladakh contact. The rnetasedimentary and metavolcanic sequences of the Greenstone Complex include limestone horizons that have yielded post-Valanginian fossils. The Karakorum Metamorphic Complex includes orthogneiss domes of granitoids intruded into the surrounding metasedimentary formations. A syenitic dome of granitoid at Hemasil is apparently syntectonic. Two phases of deformation are observed in Karakorum and Ladakh and seem to correspond, but with different grades of metamorphism. The late doming structures are characteristic of the Karakorum. The Himalaya-Karakorum contact varies from south to north, from a normal fault to a strike-slip shear zone, and finally a thrust fault. The original Ladakh Karakorum contact (Shyok Suture) is folded and reactivated by late brittle thrusting, possibly the latest large-scale deformation of the region. The closure of the Ladakh-Kohistan back-arc basin followed by the collision of India is mostly overprinted by the recent structures.